Transgender and transsexual women: effectiveness of the right to freedom, equality and dignity of the human person in the absence of legislation and public policies to combat prejudice and discrimination in the country (Revista do Tribunal Regional Federal da 3ª Região, 2019)
According to the 1988 Constitution, one of the fundamental objectives of the Federative Republic of Brazil is to promote the good of all, without prejudice of origin, race, sex, color, age and any other forms of discrimination. Unfortunately, however, the country is still far from being an unprejudiced society and does not discriminate against people because of a variety of factors, especially with regard to sexual orientation and gender identity. It is true that in recent years, as a society, we have advanced in the recognition of the differences of individuals, in freedom and autonomy, in relation to issues of sexual orientation, gender and affective relations. However, Brazil is still, admittedly, a society that discriminates and commits innumerable forms of violence against transgenders, transsexuals and the LGBT population. It is important to deal with some basic concepts and ideas on the subject presented, to outline the main rights already conquered in the legal system, and to point out the lack of effective regulation regarding the rights of Trans people in the legislation in force in the country, only by raising the debate about the issue, we can contribute to the judiciary and society to be open to sexual and gender diversity, and thus committed to the promotion of equality and freedom of all individuals. Protecting the rights of transgender, transgender and LGBT people with fair, uniform legislation in force in every country, as well as formulating efficient public policies, would contribute significantly to the fight against discrimination, prejudice and social exclusion existing in Brazil today.
Keywords: women; human rights; freedom; equality; self-determination; gender diversity; transgender; right; philosophy of Law